TH2.11 The influence of sarcopenia and systemic inflammation on survival in resected pancreatic cancer. (9th August 2022) - Bryce, Adam; Dreyer, Stephan; Chang, David
Abstract: Aims: Sarcopenia, cachexia and systemic inflammation are early hallmarks of pancreatic cancer. The impact of these processes on survival has been demonstrated in other cancer types using image-based body composition analysis. We sought to determine the impact of sarcopenia and systemic inflammation on survival in pancreatic cancer. Methods: A database of patients with pancreatic cancer undergoing resection with curative intent was maintained. Single-slice (L3) skeletal muscle index from pre-operative CT was used to define sarcopenia. Pre-operative systemic inflammation measures were curated (modified Glasgow Prognostic Score and neutrophil-lymphocyte ratio). Results: 176 patients underwent resection. Median post-operative survival was 26.3 months and 95 were sarcopenic (54%). Sarcopenia was not associated with worse survival versus non-sarcopenia (median 24.2 months vs 27.4 months, p = 0.558). mGPS was raised in 52 patients (30%) however this was not associated with worse survival versus normal mGPS (median 26.2 months vs 26.6 months, p = 0.193). Raised NLR did not significantly influence survival. Conclusions: Pancreatic cancer represents a complex biological process with survival likely influenced by tumour biology and the relationship between tumour epithelium and tumour microenvironment. Survival has previously been shown to be influenced by sarcopenia in all patients with pancreatic cancer, suggesting selection of "fitter" patients for resection in our cohort. Further understanding of tumour biology is needed to determine the relationship between tumour epithelium, tumour microenvironment, cachexia and systemic inflammation. Analysis of this relationship is ongoing and we envisage presenting results of this research in conjunction with this abstract if selected for presentation.